2014
DOI: 10.1080/15222055.2014.920747
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Rearing Density on Growth, Fin Erosion, Survival, and Migration Behavior of Hatchery Winter Steelhead

Abstract: Juvenile winter steelhead Oncorhynchus mykiss at Eagle Creek National Fish Hatchery in Estacada, Oregon, were reared for three brood years (2004–2006) at raceway densities of 7,500 (214 fish/m3), 15,000 (429 fish/m3), and 22,500 fish (643 fish/m3) to determine the effects of rearing density on growth, fin erosion, survival, adult yield, and migration behavior. Coded wire tags were used to evaluate adult survival, and fish were radio‐tagged to monitor migration times from the hatchery to the mouth of Eagle Cree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Although several studies have evaluated aquaculture techniques (i.e., cage culture, diet improvement, polyculture and thermal regimes) to facilitate Bonytail growth (Henne et al, ; Kappenman et al, ; Sowka & Brunkow, ), the effect of uncontrolled recruitment on growth rates of production fish has not been evaluated. The use of biological controls has been shown to greatly reduce densities (Kavanagh & Olson, ; Ward & Slaney, ; Ward et al, ; Westers, ), and, indeed, our results demonstrated Colorado Pikeminnow to be effective at reducing total biomass. The outcome of this effect was an increase in adult Bonytail growth rates (ΔTL, Δg, %BW and SGR), suggesting polyculture of these two species can improve conservation measures (i.e., augmentation) implemented to aid Bonytail recovery.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Although several studies have evaluated aquaculture techniques (i.e., cage culture, diet improvement, polyculture and thermal regimes) to facilitate Bonytail growth (Henne et al, ; Kappenman et al, ; Sowka & Brunkow, ), the effect of uncontrolled recruitment on growth rates of production fish has not been evaluated. The use of biological controls has been shown to greatly reduce densities (Kavanagh & Olson, ; Ward & Slaney, ; Ward et al, ; Westers, ), and, indeed, our results demonstrated Colorado Pikeminnow to be effective at reducing total biomass. The outcome of this effect was an increase in adult Bonytail growth rates (ΔTL, Δg, %BW and SGR), suggesting polyculture of these two species can improve conservation measures (i.e., augmentation) implemented to aid Bonytail recovery.…”
Section: Discussionsupporting
confidence: 76%
“…Fish & Wildlife Service); however, in hatchery ponds they are precocious, with individuals reproducing as early as Age‐2 (Hamman, ). Contradictory to positive outcomes associated with natural recruitment within a hatchery system (i.e., increased production), recruitment can have negative impacts on various factors related to overcrowding (Kavanagh & Olson, ; Tatara, Riley, & Scheurer, ; Westers, ). Using polyculture techniques, integrating fish as biological controls, has been shown to effectively control unwanted biota (i.e., non‐native species, pathogen transmitting vectors) and positively effect factors related to fish and the hatchery environment (Chaichana & Jongphadungkiet, ; Frenkel & Goren, ; Lemmens, Mergeay, Vanhove, Meester, & Declerck, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), rearing fish in ponds rather than raceways (Zydlewski et al. ), and decreasing densities in hatcheries (Kavanagh and Olsen ) can improve the physical condition, growth, and survival of hatchery‐reared salmonids. However, the benefits of such actions must outweigh the costs of production and warrant further research in hatchery‐supported southern Appalachian Mountain trout streams.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of decreased feeding and the lack of isotopic incorporation may be particularly useful in guiding hatchery and stocking procedures. For instance, enhancing instream structure in hatcheries (Brockmark et al 2007), rearing fish in ponds rather than raceways (Zydlewski et al 2003), and decreasing densities in hatcheries (Kavanagh and Olsen 2014) can improve the physical condition, growth, and survival of hatcheryreared salmonids. However, the benefits of such actions must outweigh the costs of production and warrant further research in hatchery-supported southern Appalachian Mountain trout streams.…”
Section: Sourcementioning
confidence: 99%